Teachers' Error Correction Strategies of Students' Writing at Senior High School in Pekanbaru - Tiara Ramadhani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
The purpose of this study was to explore error correction strategies of students’ writing used by English teachers at first grade students of Senior High School in Pekanbaru. There were three questions contained in this study. Firstly, what are strategies that English teachers used in correcting student’s writing. Secondly, how did English teachers implement the error corection strategies. Thirdly, factors influenced the implementation of the strategies. This study used qualitative descriptive research. The data were collected from English teachers and three students of each selected school (SMAN 7 Pekanbaru, SMA Plus Binabangsa Pekanbaru, and SMA Muhammadiyah 1 Pekanbaru) by using observations, interviews, and document analysis. The text used in this study was descriptive text. Result of the data analysis showed that English teachers used self-corection, peer-correction, and teacher-correction in correctiong students’ writing. In teacher-correction, they also used one-to-one correction and correction code to improve students’ writing. To implement error correction strategies, English teachers used familiar theme, tried to improve students’ vocabularies, and applied the process of writing. Then, there were some factors influenced English teacher implement error correction strategies. Those factors mostly because students had insufficient vocabularies and the other factors was English teachers did not have enough time in correcting students’ writing. In conclusion, these findings implied the teachers should try to use an effective error correction strategies, like one-to-one correction strategy in order to get good results for the students.